EFFECTS OF AQUEOUS LEAVES EXTRACT OF CASSIA GLAUCA LAM. IN STREPTOZOCIN-INDUCED DIABETIC RATS - Jalalpure, S. S.; Salahuddin, Md. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Cassia glauca Lam. is a glabrous tree belonging to family Caesalpiniacea, found throughout India, tropical Asia and Australia. In folk medicine, leaves of Cassia glauca are used for the treatment of diabetes. The aim of this study therefore, was to investigate the antihyperglycemic and antidiabetic activity of aqueous extract of Cassia glauca leaves. The various parameters studied included effect on normoglycemic, oral glucose tolerance test, hypoglycemic activity in streptozotocin induced diabetic rats, fasting blood glucose levels, changes in body weight, serum lipid levels, liver glycogen content, serum insulin level and glycated hemoglobin in diabetic control and treatment rats. On oral administration, aqueous extract of Cassia glauca leaf at a dose of 500 mg/kg did not show significant effect on blood glucose levels in normoglycemic rats, whereas aqueous extract showed statistically significant (P < 0.05) effect by reducing the effect of external glucose load. In chronic model of diabetis, aqueous extract of Cassia glauca leaf at a dose of 500 mg/kg and glibenclamide (0.25 mg/kg) were administered for 21 days. At the end of the treatment period there was significant increase in the body weight, liver glycogen, serum insulin level and the HDL cholesterol levels. There was a significant decrease in fasting blood glucose, glycated hemoglobin, total cholesterol and serum triglycerides, thus providing support to the potent antidiabetic property of the plant extract.